Electronically adjustable PD controller using OTAs - Petchmaneelumka, Wandee; Cheypoca, Thepjit; Riewruja, Vanchai (My University, 2011)
A method for realizing the PD controller is presented in this paper. The circuit implementation is based on operational transconductance amplifiers (OTAs) as active elements with a grounded capacitor. The proportional gain and derivative time can be electronically varied by tuning the external bias current of OTA. Moreover, the structure of the proposed scheme can be simply realized the PID controller by including resistor-capacitor series network at the output terminal. Experimental results verifying the performances of the proposed circuit are in close agreement with the theoretical values. © 2011 SICE.
Keywords: electronically adjusting property; OTA; PD controller